Универсальная концепция прав человека : миф или реальность? - Мишина, Наталья Викторовна; Мішина, Наталія Вікторівна; Mishina, Natal'ja (My University, 2012)
The article discusses the advantages and disadvantages of a universal concept of human rights in terms of whether it should be used for further improvement of the legal regulation of the human rights and freedoms in Ukraine. Based on these arguments, it is concluded that it is more correct to speak not of the universal, but the Western concept of human rights. Author concludes that at the current stage of historical development the most optimal situation is in which each country will have its own system of human rights, created with the features of the national constitutional law in light of international legal standards.
Мишина Н. В. Универсальная концепция прав человека : миф или реальность? / Н. В. Мишина // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2012. – Т. 11. – С. 118-126.
Keywords: права человека; международные стандарты; универсальная концепция прав человека; права людини; міжнародні стандарти; універсальна концепція прав людини; human rights; international standards; universal concept of human rights